Measuring somatic symptoms with the PHQ-15: a comparative study of three Iranian samples. Issue 3 (20th April 2020) - Dadfar, Mahboubeh; Asgharnejadfarid, Ali Asghar; Hosseini, Agha Fatemeh; Esfahani, Mehdi Nasr; Lester, David; Kalibatseva, Zornitsa
ABSTRACT: Somatic symptoms are among the most common presenting concerns in the primary care. The theoretical literature has proposed that Iranians may somaticize distress. The aims of the study were (a) to compare somatic symptoms among three Iranian samples, (b) to explore gender-related differences, and (c) to investigate the psychometric properties of the Patient Health Questionnaire-15 (PHQ-15). A total of 349 Iranian participants (94 college students, 100 elderly persons, and 155 psychiatric outpatients) were recruited. Psychiatric outpatients scored higher on somatic symptoms than college students. Females in all samples scored higher than males. The measure in all samples demonstrated good internal consistency and reliability as well as moderate concurrent and discriminant validity. For each sample identified four slightly different factors, which covered gastrointestinal, pain, psycho-fatigue, cardiopulmonary, and reproductive symptoms. Implications for culturally appropriate services are discussed. This study provides evidence for the usefulness of the PHQ-15 for assessing somatic symptoms in three Iranian samples and extends existing research about the measure's factor structure.